1992
DOI: 10.1055/s-2008-1033006
|View full text |Cite
|
Sign up to set email alerts
|

Radiologische Befunde beim Adamantinom der langen Röhrenknochen

Abstract: The radiological findings of adamantinomas of long bones are described in 22 patients. The diagnosis was confirmed by a team of experts (pathologist, radiologist, orthopaedic surgeon) of the "Bone tumour study group" at the German Cancer Research Center. There were 12 male and 10 female patients aged 5 to 67 years (most commonly in the second and third decade). In 21 patients the tibia was involved and in one patient the fibula. The tumour was nearly always in the diaphysis (20 cases). The most striking radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This part of the bone is slightly expanded, deformed, the tumor has a cystic or more often a multiloculated appearance with more or less sclerotic rim. The cortical bone is thinned, in other cases partially or extensively destroyed without any periosteal reaction [29].…”
Section: Discussionmentioning
confidence: 99%
“…This part of the bone is slightly expanded, deformed, the tumor has a cystic or more often a multiloculated appearance with more or less sclerotic rim. The cortical bone is thinned, in other cases partially or extensively destroyed without any periosteal reaction [29].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor has a cystic, multilocated feature with a sclerotic rim. The cortical bone is thinned and ultimately destroyed without any periosteal reaction (22).…”
Section: Discussionmentioning
confidence: 99%
“…Examining flow cytometry and p-53 expression, IHC studies demonstrated up to 48% expression of p53 proteins in all classical subtypes [33] , [34] . P-63 is also a reliable marker in adamantinomas [35] . E-, P- and N- cadherin, as well as osteonectin are expressed in classical subtype whereas in OFD adamantinoma expression of nuclear factor kB ligand, macrophage cerebrospinal fluid and osteoclastogenic factors are seen [29] , [36] .…”
Section: Introductionmentioning
confidence: 98%